การประยุกต์ใช้การวิเคราะห์กลุ่มแฝงเพื่อศึกษาลักษณะการเรียนรู้ตลอดชีวิตของนักศึกษาระดับปริญญาตรี - พิมผกา อ้อมอารี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this research is 1) to verify the structural validity of the lifelong learning measurement model of undergraduates’ 2) to verify the cross-validation of the lifelong learning measurement model of undergraduates’ and 3) to arrange group and study of undergraduate’ relationships, distinguished characteristics by gender year and field of study from 1,148 samples, the samples were examined in Multi-Stage Sampling by Lifelong Learning Students’ Behavior Questionnaire. The result of content validation by Item - Objective Congruence (IOC) score 0.80 - 1.00, the discrimination levels by Item Total Correlation (rxy) of 0.367- 0.734 and reliability coefficients by Cronbach's Alpha (α) at 0.963. The data is analyzed by Descriptive Statistics, Confirmatory Factor Analysis (2ndCFA) and Latent Profile Analysis (LPA). The Study findings summarized as following: 1) The structural model of Lifelong Learning of undergraduate students fitted well with the empirical data by 2 = 95.992, df = 94, CFI =1.000, TLI = 0.999, RMSEA = 0.006, SRMR = 0.023 แ ล ะ p-value = 0.423.The undergraduates’ lifelong learning assessment consequently consist of 3 elements 17 indicators: the most influential factor is respectively to think, to manage and to develop and to communicate and to access information.2. The result of cross validation test found that the construct validity model generates a good fit with following results: 2 = 97.199, df = 94, CFI = 0.999, TLI = 0.999, RMSEA = 0.008, SRMR = 0.022 and p-value = 0.390. Consequence accordingly, it indicates that the measurement model has a representative with the approximate weighted value factor of standard score as Δ 2 = 1.207, Δ df = 0 3. The students’ results classification, according to the undergraduates’ lifelong learning characteristics, it’s shown that there are essentially 3 student groups. Group 1, 187 students ( 3 2 .6 3 %) need to be accelerated for lifelong learning. Group 2, the student group that lead to lifelong learning, consisting of 70 students (12.22%) and Group 3, composing of 316 students (55.15%) who are eager for lifelong learning. the consequence of groups category, it appears as Likelihood = -6,679.845, Entropy (Ek) = 0.903, AIC = 13,499.69, BIC = 13,804.252 and ABIC = 13,582.032. To summarize, the undergraduates’ lifelong learning, classified by gender, year, and field of study, found that the gender and year of the students do not correlate with the differences of lifelong learning groups. On the contrary, the field of study group is affiliated with the differences of lifelong learning groups with statistical significance at the level of 0.01